Representasi Santri Milenial dalam Wacana Literasi Digital di Instagram (Analisis Wacana Kritis Norman Fairclough pada Instagram: @elmahrusy) - Moh. Ihya’u Hafidh (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2023)
This study aims to analyze the representation of millennial students in digital literacy on Instagram using Norman Fairclough's critical discourse analysis. This study describes how millennial students represent themselves in the context of digital literacy through popular social media platforms such as Instagram. A critical discourse analysis approach is used to reveal the power relations involved in this representation. This research method involves analyzing visual and text content uploaded by millennial students on their Instagram accounts. This study's results indicate that millennial students' representation of digital literacy on Instagram is strongly influenced by their cultural, religious, and social context factors. They use Instagram to express their religious identity, share religious knowledge, and promote Islamic values relevant to the digital era. However, there are also constructions of representation that face conflict with the dominant narrative. Millennial students face challenges in navigating the complex digital literacy space, often facing negative stereotypes or discrimination. This research identifies the efforts of millennial students to challenge negative narratives and build strong communities on Instagram. Thus, this research provides a deeper understanding of the representation of millennial students in digital literacy on Instagram. The implications of this research can be used to strengthen the role of millennial Santri in influencing public narratives and promoting a better understanding of Islam in the digital era.